Hubungan Jumlah Leukosit Dengan Defisit Fungsional Neurologis Pada Pasien Stroke Iskemik - Oktavia, Farah Mila, Dr. Iwan Setiawan, M.Kes., Sp.S (2017)
Stroke is brain function disorder that occurs suddenly due to vascular disorders and can lead to death, which lasted for 24 hours or more and will lead to circulatory disorders. Stroke is the most common primary cause of death in most developed countries, coronary heart disease and cancer. Inflammation that occurs in the acute phase of cerebral ischemia will increase the damage to areas of the brain after ischemic events. Higher levels of Leukocytes can predict poorer clinical presentation and poor functional outcomes. The objective is to determine whether there is a relationship leukocyte count with functional neurological deficit levels in PKU Hospital Aisyiyah Boyolali and Karanganyar District Hospital. The methods of research, this research method using observational analytic cross sectional method to determine the relationship of the number of leukocytes with neurological functional deficits in patients with ischemic stroke. Results of research are obtained 3 patients out of 17 patients with ischemic stroke with severe neurological deficits in patients with ischemic stroke normal leukocytes, whereas in patients with ischemic stroke elevated leukocyte found in 10 patients out of 17 patients with ischemic stroke who had severe neurological deficits. From the analysis of test Fisher's statistical test obtained by value p = 0.006 (p <0.05). There is a relationship between the amount of leukocyte and functional neurological deficits in patients with ischemic stroke.